Letter from Louis A. Baptista to Jane Tolmach - Louis A. Baptista:::::: (1973)
A letter from Louis A. Baptista to Jane Tolmach congratulating her on her election the the position of Mayor of Oxnard and requesting that she work to keep the State Hospitals open.